Diversity and abundance of hymenopteran parasitoids at two different elevations in Redang Island, Terengganu, Malaysia - Salmah, Mohamed; Mohammad Aliff Fahmi, Harun; Marina, Roseli (2021)
A study was conducted to determine the diversity and abundance of hymenopteran parasitoids in two different elevations of the coastal and inland forest of Redang Island, Terengganu. Three Malaise traps were installed at each three sampling points in both plots, respectively. The insect samples were collected after seven days and brought to the laboratory for sorting, enumeration, and identification process up to family level. The abundance of parasitoids between two plots was compared using T-test analysis while the comparison of hymenopteran parasitoids abundance between different families was analysed using one-way Analysis of Variance (ANOVA). The insect diversity was analysed using the Shannon-Weiner Diversity Index (H’). Overall, there were 48 individuals of parasitoids from 13 families were collected and no significant difference (P>0.05) of parasitoids abundance between both plots. However, the parasitods population in inland forest was more diverse (H’=1.58) compared to the coastal forest (H’=1.42). Thus, there was a significant difference (P<0.05) of parasitoids abundance among the 13 different hymenopteran families. The most abundant family was Braconidae with 24 individuals followed by Ichneumonidae with six individuals whilst the least abundant families were Elasmidae, Mutillidae, Diapriidae, Chalcididae, Eulophidae, Pompilidae, Chrysididae, and Platygastridae with only one individual, respectively. In conclusion, the diversity of hymenopteran parasitoids in the inland forest was higher than coastal forest although the abundance was not significantly different. Other parameters such as vegetation species and distribution, and abiotic factors should be considered in future studies in order to de